IMPLEMENTASI EMPLOYABILITY SKILLS PADA SMK PROGRAM KEAHLIAN AKUNTANSI BIDANG KEAHLIAN BISNIS MANAJEMEN - Tri Kuat (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
The purpose of this study is to determine the implementation of employability skills and level of achievement on SMK Accounting Expertise Program of Business Management Expertise. This research uses quantitative and qualitative methods.Collection data by observation, interview, and documentation. Place of research in SMK N 6 Surakarta and SMK N 1 Sukoharjo. Analysis data with descriptive qualitative and quantitative. The results of this study show that the implementation of employability skills in SMK Accounting Expertise Program of Business Management Expertise at SMK N 6 Surakarta is very good because of the seven core competency competencies have been largely held at the highest level, while in SMK N 1 Sukoharjo into the good category, Because most controlled at the middle level. While the achievement level of employability skills at SMK Accounting Expertise Program of Management Business Expertise at SMK N 6 Surakarta level one 0%, level two equal to 34,30%, and level three equal to 65,70%. While in SMK N 1 Sukoharjo which controls one level of 17,10%, level two equal to 54,30%, and level three equal to 28,60%.